Entrepreneurship in Social Media Literacy and Intentions for Diabetes Prevention among Adolescent Students - Pratiwi, Ika Nur; Prabawati, Dita Dwi Oktav; Wahyuni, Erna Dwi; Nursalam, Nursalam; Widyawati, Ika Yuni; Yahaya, Nor Aziyan (Pandawan, 2026)
Diabetes Mellitus (DM) prevention behavior is essential for reducing DM incidence among adolescents, a population increasingly exposed to lifestyle risks and heavily engaged with digital platforms. Social media provides a promising channel for health promotion, yet limited evidence explains how literacy in this medium supports preventive behaviors. This study aims to analyze the correlation between social media literacy and intention with DM prevention behavior among adolescent students. A cross-sectional design with purposive sampling was conducted involving 231 students aged 16 years in East Java, Indonesia. Data were collected using questionnaires measuring social media literacy, intention, and DM prevention behavior, while Spearman’s rho correlation <0.05 was applied for analysis. Descriptive findings showed that 58% of participants were female, 67.1% used more than three social media platforms, 39% accessed social media 3–4 hours daily, and 4.3% had a family history of DM. The analysis revealed significant positive correlations between social media literacy (p<0.001, r=0.325) and intention (p<0.001; r=0.305) with DM prevention behavior. Adolescents with higher literacy and stronger intentions were more likely to exhibit proactive DM prevention actions. These results demonstrate that emerging technologies, particularly social media, hold substantial potential as promotive and preventive tools for adolescent health. Enhancing social media literacy can improve adolescents’ ability to identify, interpret, and apply credible health information, supporting healthier behavioral choices. The study suggests that integrating digital health literacy into adolescent-focused programs may strengthen early preventive efforts and reduce future DM risk.